2018
DOI: 10.1007/s00265-018-2620-5
|View full text |Cite
|
Sign up to set email alerts
|

Temperature alters multimodal signaling and mating success in an ectotherm

Abstract: Temperature affects ectotherms in a variety of ways. These effects can be especially complex in sexual behaviors, as different sexes may be affected differently by temperature. We examined this in the jumping spider, Habronattus clypeatus. In this species, males court females using visual and vibratory signals. We tested whether key intersexual behaviors would change with temperature in similar, predictable ways across males and females. We first measured temperature and apparent activity of individuals across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 66 publications
1
41
0
Order By: Relevance
“…Here, we found that patterns of thermal variation in courtship activity relate to overall mating rates across temperatures. However, the patterns of sex specificity in thermal sensitivity we found as well as the potential for one sex to constrain mating rates more than the other suggest that courtship activity alone may not be a consistent predictor of thermal sensitivity in mating (see also Brandt et al, 2018). Alternatively, temperature‐related breakdowns in reproduction may emerge from a combination of physiological and behavioral processes that occur throughout mating interactions.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Here, we found that patterns of thermal variation in courtship activity relate to overall mating rates across temperatures. However, the patterns of sex specificity in thermal sensitivity we found as well as the potential for one sex to constrain mating rates more than the other suggest that courtship activity alone may not be a consistent predictor of thermal sensitivity in mating (see also Brandt et al, 2018). Alternatively, temperature‐related breakdowns in reproduction may emerge from a combination of physiological and behavioral processes that occur throughout mating interactions.…”
Section: Discussionmentioning
confidence: 79%
“…The shape of thermal activity curves for courtship and mating behaviors may differ considerably from other traits and may be difficult to predict from thermal performance curves of physiological rates. For example, female Habronattus clypeatus jumping spiders are most likely to mate at hot temperatures, even though male courtship activity does not appear constrained at much lower temperatures in a laboratory environment and general activity is highest for both sexes at cooler temperatures in the field (Brandt et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations